3D design of steel structures with considering nonlinear base shear distribution and seismic energy. (March 2022) - Ghamari, Masoud; Shooshtari, Mohammad; Homaei, Hossein
Abstract: Current seismic design codes use lateral load distributions that do not consider 3D structural behavior, nonlinear structural state, and soil-structure interaction. Moreover, calculated seismic force does not reflect the energy content of the earthquake and record-to-record variability in its lateral distribution. This research proposes a new design procedure for steel structures that reach nonlinear state to address the mentioned shortcomings. First, nine 3D 6-story steel structures in 3 different soil types and three different structural systems are analyzed under 12 earthquakes for each soil type. Soil-structure interaction is taken into account using the cone model. Then, the general behavior of the structures in terms of the nonlinear base shear distribution, the relationship between the seismic input energy and the induced force, and the effect of the structural systems and the site categories are investigated. In the second phase of the study, two of the structures with the same soil type are analyzed using 94 motions to study the record-to-record variability. Finally, the two structures are designed according to the proposed procedure, and their performance is compared with those designed using the current code. The results indicate that the new method leads to remarkably better structural behavior. Furthermore, nonlinear base shear distribution in the 3D state is predictable even in the presence of record-to-record variability and nonlinearity.